Strategic sourcing: dashboarding a spend analysis to support decision-making - Rodrigues, Sérgio Manuel dos Anjos (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence